(untitled) - Wiener-Kronish, Jeanine P. (Philadelphia, 2001)
This book is a comprehensive review of conscious sedation in both the inpatient and outpatient settings. The authors review guidelines and requirements for office-based conscious sedation, including medicolegal issues.
Keywords: An thần,Gây mê tĩnh mạch,Intravenous anesthesia,Conscious sedation